Endophytic Bacillus velezensis XS142 is an efficient antagonist for Verticillium wilt of potato - Li, Min; Yang, Jianfeng; Li, Haoyu; Wang, Yating; Cheng, Xu; Han, Guodong; Bisseling, Ton; Zhao, Jun (Frontiers in Microbiology, 2024)
Potato Verticillium Wilt (PVW) caused by Verticillium dahliae is a vascular disease, that seriously affects potato (Solanum tuberosum L.) yield and quality worldwide. V. dahliae occupies the vascular bundle and therefore it cannot efficiently be treated with fungicides. Further, the application of these pesticides causes serious environmental problems. Therefore, it is of great importance to find environmentally friendly biological control methods. In this study, bacterial strains were isolated from agricultural lands on which potato had been cultured for five years. Five strains with a broadspectrum antagonistic activity were selected. Among these five strains, Bacillus velezensis XS142 showed the highest antagonistic activity. To study the mechanism of XS142, by which this strain might confer tolerance to V. dahliae in potato, the genome of strain XS142 was sequenced. This showed that its genome has a high level of sequence identity with the model strain B. velezensis FZB42 as the OrthoANI (Average Nucleotide Identity by Orthology) value is 98%. The fungal suppressing mechanisms of this model strain are well studied. Based on the genome comparison it can be predicted that XS142 has the potential to suppress the growth of V. dahliae by production of bacillomycin D, fengycin, and chitinase. Further, the transcriptomes of potatoes treated with XS142 were analyzed and this showed that XS142 does not induce ISR, but the expression of genes encoding peptides with antifungal activity. Here we showed that XS142 is an endophyte. Further, it is isolated from a field where potato had been cultured for several years. These properties give it a high potential to be used, in the future, as a biocontrol agent of PVW in agriculture.